The knowledge deficit: Liquid words as neo-liberal technologies. (1st September 2012) - Hassan, Robert
The essay argues that the dynamic conjunction of neo-liberal globalization and the information technology revolution has created not only a new relationship with time – which itself is having an immensely consequential (if under-theorized) effect – but also a transformed relationship with the written word. Today reading and writing are increasingly conducted through liquid crystal display – a new technological form of the ancient technology of the printed word. The printed word has become liquid. This essay argues that liquid and accelerated and burgeoning volumes of words that are overwhelmingly oriented towards market-driven instrumentalized ends are creating a deficit in the accumulation and tradition of critical knowledge production and its dissemination. The negative effects of the knowledge deficit are manifold, but the most salient is in the realm of politics, where questions of power, agency and the democratic process become increasingly problematic.